IMPLIKASI HUKUM PINJAMAN ONLINE: KAJIAN TERHADAP PERLINDUNGAN NASABAH DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM - Nurmiana; Samsulijar (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The development of information technology has given rise to various innovations in the financial sector, one of which is online lending services (pinjol). Although providing convenience, online lending practices often raise legal issues, particularly regarding customer protection. This paper examines the legal implications of online lending practices and analyzes legal protection for customers from both the perspective of positive law in Indonesia and Islamic law. The method used is a normative legal approach with qualitative analysis. The findings reveal that despite existing regulations such as the Consumer Protection Law and POJK, their implementation remains ineffective. In Islamic law, online lending practices involving usury and exploitation are contrary to the principles of justice and balance in muamalah.